2009
DOI: 10.1073/pnas.0811599106
|View full text |Cite|
|
Sign up to set email alerts
|

Laminin-111 protein therapy prevents muscle disease in the mdx mouse model for Duchenne muscular dystrophy

Abstract: Duchenne muscular dystrophy (DMD) is a devastating neuromuscular disease caused by mutations in the gene encoding dystrophin. Loss of dystrophin results in reduced sarcolemmal integrity and increased susceptibility to muscle damage. The α 7 β 1 -integrin is a laminin-binding protein up-regulated in the skeletal muscle of DMD patients and in the mdx mouse model. Transgenic overexpression of the α 7 -integrin alleviat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
109
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(116 citation statements)
references
References 27 publications
5
109
0
Order By: Relevance
“…Studies have indicated that the 71 integrin might act to modulate the organization and deposition of the muscle extracellular matrix (Colognato et al, 1999;Rooney et al, 2009a). To investigate the mechanism by which enhanced 7 integrin expression improved the myopathic phenotype in the absence of the laminin-211-laminin-221 ligand, we examined changes in levels of other ;itga7+ animals have 7-fold and 2.9-fold more galectin-3 protein compared with that in both wildtype and dy W-/-animals, respectively (***P<0.001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have indicated that the 71 integrin might act to modulate the organization and deposition of the muscle extracellular matrix (Colognato et al, 1999;Rooney et al, 2009a). To investigate the mechanism by which enhanced 7 integrin expression improved the myopathic phenotype in the absence of the laminin-211-laminin-221 ligand, we examined changes in levels of other ;itga7+ animals have 7-fold and 2.9-fold more galectin-3 protein compared with that in both wildtype and dy W-/-animals, respectively (***P<0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Cryosections from 4-week-old TA and diaphragm muscle were stained using hematoxylin and eosin, as previously described (Rooney et al, 2009a), and were used to determine the percentage of myofibers that contained CLN using a Zeiss Axioskop 2 Plus fluorescence microscope. A minimum of 1000 fibers per animal (five animals per group) were counted and the percentage of myofibers with CLN calculated.…”
Section: Hematoxylin and Eosin Stainingmentioning
confidence: 99%
“…27 . The most advanced approach is via delivery of Laminin-111 protein, although the efficacy remains low and the need to produce a large amount of bioactive protein is challenging 27 .…”
Section: E)mentioning
confidence: 99%
“…27 . The most advanced approach is via delivery of Laminin-111 protein, although the efficacy remains low and the need to produce a large amount of bioactive protein is challenging 27 . In addition, the utilization of CRISPR/dCas9 system to upregulate Lama1 in mdx mice has been achieved locally via electroporation, which is not easily translatable into clinical settings 28 .…”
Section: E)mentioning
confidence: 99%
“…14 LM-111 supplementation has demonstrated remarkable regenerative capacity in several models of muscular disease [15][16][17] and injury, 18 primarily by enhancing satellite cell activity. In mice with congenital muscular dystrophy due to missing LM α 2 chains, overall health and survival can be improved by administration of LM α1 chains, 19,20 In vitro, LM-111 promotes muscle stem cell proliferation and differentiation to a greater extent than other ECM components such as collagen type I and fibronectin.…”
Section: Skeletal Muscle Regenerationmentioning
confidence: 99%